Role of the SLIT-ROBO signaling pathway in renal pathophysiology and various renal diseases - Feng, Li; Shu, Hua-Pan; Sun, Lu-Lu; Tu, Yu-Chi; Liao, Qian-Qian; Yao, Li-Jun (Frontiers in Physiology, 2023)
SLIT ligand and its receptor ROBO were initially recognized for their role in axon guidance in central nervous system development. In recent years, as research has advanced, the role of the SLIT-ROBO signaling pathway has gradually expanded from axonal repulsion to cell migration, tumor development, angiogenesis, and bone metabolism. As a secreted protein, SLIT regulates various pathophysiological processes in the kidney, such as proinflammatory responses and fibrosis progression. Many studies have shown that SLIT-ROBO is extensively involved in various aspects of kidney development and maintenance of structure and function. The SLIT-ROBO signaling pathway also plays an important role in different types of kidney disease. This article reviews the advances in the study of the SLIT-ROBO pathway in various renal pathophysiological and kidney disorders and proposes new directions for further research in this field.